Influence of the Casein Genotype on Goat Milk Bioactivity: An In Silico Analysis of the Casein Peptidome - Aram Y. Rubio-Reyes; Iván Delgado-Enciso; Eduardo Casas; Estela Garza-Brenner; Ana M. Sifuentes-Rincón (Molecules, 2025)
Goat caseins are highly polymorphic proteins that affect milk functional properties. In this study, an in silico approach was employed to analyze the influence of goat casein allelic variants on the quantity and bioactivity potential of peptides released after enzymatic hydrolysis. The reported protein sequences from the most frequent allelic variants in Capra hircus caseins (α-S1, β, α-S2, and κ-casein) were analyzed in the BIOPEP-UWM database to determine the frequency of occurrence of bioactive fragments from each casein. After specific hydrolysis with pepsin, trypsin, and chymotrypsin A, important differences in the peptide profile and bioactivity potential were observed within and between the casein allelic variants. The β-casein A and C alleles, α-S1-casein allele E, and α-S2-casein allele F presented the highest bioactivity potential, and some allele-specific peptides were also released, highlighting the impact of genotype on the predicted bioactivity. The inhibition of angiotensin-converting enzyme (ACE-I) and dipeptidyl peptidase IV (DPP-IV) activities was the most frequent bioactivity of the released peptides, suggesting possible antihypertensive and antidiabetic effects. Once confirmed by experimental studies, the use of goat casein genotyping could direct efforts to enhance the functional quality of goat milk.